Understanding how Universal Credit influences employment behaviour : findings from qualitative and experimental research with claimants /: findings from qualitative and experimental research with claimants. (September 2017) - Rahim, Nilufer; (Social researcher), Graham, Jenny; (Behavioural data scientist), Kiss, Zsolt; Davies, Malen
No abstract available